Fertility and Labor Force Participation in the Soviet Union and Eastern Europe - Gregory, Paul R. (The Review of Economics and Statistics, 1982)
This discussion begins with a review of the basic features of the Western neoclassical models of human capital and fertility and their counterparts that are employed in this study. This contrasts leads to the conclusion that the Western and Eastern models (in their contemporary forms) are basically identical. The agreement on the theoretical foundations of human capital analysis is bolstered by substantial agreement in the empirical results. The major comparative study of fertility and family in Eastern and Western Europe (UN 1976) failed to reveal a distinctive pattern of behavior for Eastern Europe other than its steeper decline in fertility since the mid 1950s. In general Soviet and Eastern European research (and Western studies) has yielded partial relationships similar to those found in Western countries. A simulatenous equation model of fertility female labor participation and marriage was specified and estimated using a combined time series cross section of Eastern European countries including the Soviet Union. Homogeneity tests required pooling over time and countries (except in the case of the participation equation) and the model was estimated using OLS 2SLS and Zellner-iterative techniques. The estimated equations revealed no major surprises. The labor supply of women was retarded by high fertility; higher wages drew additional women into the labor force; reductions in infant mortality lowered fertility; narrowing of the female wage differentials reduced fertility as did increases in marital instability. If there are surprises they were the positive impact of education upon fertility and the insignificant effect of female labor force participation on fertility. Simulations of the reduced form of the system revealed the direct and indirect effects of changes in exogenous variables and of shocks to intercepts. Forecasts of fertility female labor force behavior and marriage were made for the year 1990 on the basis of certain likely scenarios. All of these scenarios predicted further reductions in fertility and marriage rates and increases in female participation rates. The exercise suggests that there is no unique socialist model of population growth and labor force behavior suggesting instead that families behave similarly under radically different economic systems. There are reservations to this conclusion and the unexpected positive education effect on fertility and the insignificant female participation effect on fertility may suggest that differences in economic systems do matter in household decision making.